Requirement-oriented aspect refactoring for early aspect formation and mapping in software maintenance - Subramaniam, Hema (2016)
Modularity aims to increase the maintainability of a software program by fostering reusability, assist in reducing development cost and enhancing the quality of the software. Although modularity gaining popularity, yet it hard to be realized due to the existence of stakeholder interest in the primary programs. Thus, maintainability became an unresolved issue. This issue may be compromised by isolating stakeholder interests, yet the system still contains interests which hard to be located. Therefore, an essential approach for managing and controlling those crosscutting stakeholder interests became tremendously important. Accordingly, Aspect-Oriented Approach (AOA) is employed the concept of crosscutting concern and aspect as the representation of those stakeholder interests. At the present time, the software practitioners have preferred to conduct crosscutting concern isolation at coding level, which have been resulting in ambiguous situation. Therefore, the crosscutting concern isolation process was transformed into requirement specifications. Since Early Aspect concept stay in line with new software development, the attempt to make existing application’s to be AOA compatible became the matter in question. For this reason, the refactoring effort which started at requirement specification has become absolutely necessary. In that case, this study seeks to address the issue by proposing a conceptual framework known as Requirement-Oriented Aspect Refactoring (ReqOAR). In order to view the issue comprehensively, the ReqOAR aims to handle concern at requirement level and to facilitate aspect candidate flow throughout existing software artefacts. To foster effective concern handler at requirement level, ReqOAR conceptual framework were included with the process components such as concern identification, concern isolation and aspect formation. Whereas, to ensure the flow of aspect candidate throughout the software artefacts, ReqOAR comprise of process called as concern mapping. Apart from process components, ReqOAR also contain techniques components which associated with aforementioned process components. For instance, Crosscutting Concern Domain Library Listing (CCDLL) and Concern Associated Terms Glossary (CATG) are among the ReqOAR proposed techniques. Furthermore, ReqOAR was validated using empirical evaluation. According to the evaluation, an optimum accuracy value was recorded from the treatment technique compared to control technique. These current findings would definitely empower the growing body of AOA in the context of restructuring the requirement specification.